Higher Prevalence of “Low T3 Syndrome” in Patients With Chronic Fatigue Syndrome: A Case–Control Study - Ruiz-Núñez, Begoña; Tarasse, Rabab; Vogelaar, Emar F.; Janneke Dijck-Brouwer, D. A.; Muskiet, Frits A. J. (Frontiers in Endocrinology, 2018)
Chronic fatigue syndrome (CFS) is a heterogeneous disease with unknown cause(s). CFS symptoms resemble a hypothyroid state, possibly secondary to chronic (low-grade) (metabolic) inflammation. We studied 98 CFS patients (21-69 years, 21 males) and 99 age- and sex-matched controls (19-65 years, 23 males). We measured parameters of thyroid function, (metabolic) inflammation, gut wall integrity and nutrients influencing thyroid function and/or inflammation. Most remarkably, CFS patients exhibited similar TSH, but lower FT3 (difference of medians 0.1%), TT4 (11.9%), TT3 (12.5%), %TT3 (4.7%), SPINA-GD (14.4%), SPINA-GT (14.9%), 24-hour urinary iodine (27.6%) and higher %rT3 (13.3%). FT3 below the reference range, consistent with the 'low T3 syndrome', was found in 16/98 CFS patients vs. 7/99 controls (OR 2.56; 95% CI=1.00 - 6.54). Most observations persisted in two sensitivity analyses with more stringent cut-off values for BMI, hsCRP and WBC. We found possible evidence of (chronic) low-grade metabolic inflammation (ferritin and HDL-C). FT3, TT3, TT4 and rT3 correlated positively with hsCRP in CFS patients and all subjects. TT3 and TT4 were positively related to hsCRP in controls. Low circulating T3 and the apparent shift from T3 to rT3 may reflect more severely depressed tissue T3 levels. The present findings might be in line with recent metabolomic studies pointing at a hypometabolic state. They resemble a mild form of 'non thyroidal illness syndrome' and 'low T3 syndrome' experienced by a subgroup of hypothyroid patients receiving T4 monotherapy. Our study needs confirmation and extension by others. If confirmed, trials with e.g. T3 and iodide supplements might be indicated.